2020
DOI: 10.1007/s10936-020-09715-6
|View full text |Cite
|
Sign up to set email alerts
|

How Do Arab Tweeters Perceive the COVID-19 Pandemic?

Abstract: Language reflects several cognitive variables that are grounded in cognitive linguistics, psycholinguistics and sociolinguistics. This paper examines how Arab populations reacted to the COVID-19 pandemic on Twitter over twelve weeks since the outbreak. We conducted a lexicon-based thematic analysis using corpus tools, and LIWC and applied R language's stylo. The dominant themes that were closely related to coronavirus tweets included the outbreak of the pandemic, metaphysics responses, signs and symptoms in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…62 One thematic analysis study of 1 920 593 Arabic tweets in Egypt showed that negative emotions and sadness were high in tweets showing affective discussions, and the dominant themes included the outbreak of the pandemic, metaphysics responses, signs and symptoms in confirmed cases, and conspiracism. 64 In Singapore, Lwin and colleagues examined 20 325 929 tweets using sentiment analysis and showed that public emotions shifted over time: from fear to anger and from sadness to gratefulness. 77 Chang and colleagues examined over 1•07 million Chinese texts from various online sources in Taiwan using deductive analysis and identified that negative sentiments mainly came from online news with stigmatising language linked with the COVID-19 pandemic.…”
Section: Social Media For Surveillance and Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…62 One thematic analysis study of 1 920 593 Arabic tweets in Egypt showed that negative emotions and sadness were high in tweets showing affective discussions, and the dominant themes included the outbreak of the pandemic, metaphysics responses, signs and symptoms in confirmed cases, and conspiracism. 64 In Singapore, Lwin and colleagues examined 20 325 929 tweets using sentiment analysis and showed that public emotions shifted over time: from fear to anger and from sadness to gratefulness. 77 Chang and colleagues examined over 1•07 million Chinese texts from various online sources in Taiwan using deductive analysis and identified that negative sentiments mainly came from online news with stigmatising language linked with the COVID-19 pandemic.…”
Section: Social Media For Surveillance and Monitoringmentioning
confidence: 99%
“…46 One thematic analysis study of 1,920,593 Arabic tweets in Egypt revealed that negative emotions and sadness were loaded in tweets showing affective discussions, and the dominant themes included "the outbreak of the pandemic," "metaphysics responses," "signs and symptoms in confirmed cases," and "conspiracism." 47 In Singapore, Lwin et al examined 20,325,929 tweets using sentiment analysis and showed the public emotions shifted over time:…”
Section: Public Sentimentmentioning
confidence: 99%
“…The international media actively reported the research results of national health organizations and the World Health Organization (WHO), such as the source, symptoms, mode of transmission, and harm of the virus. The perception about COVID-19 pandemic has also been globally tweeted (Essam & Abdo, 2020). Today, the outbreak has become a public health event, so the dynamic surroundings are relevant to everyone's safety.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that there were significant differences in the discourse about the epidemic of different groups on social platforms. For instance, one study found that among the contents related to the COVID-19 posted by Arab twitters, topics related to religion and health were dominant and generally passive (Essam & Abdo, 2020), which was also the case in Malaysia that the majority of the online letters associated the COVID-19 with negative expressions (Joharry & Turiman, 2020). On the contrary, another similar study carried on African Americans found they held a positive attitude towards fighting against the epidemic (Odlum et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%